Profiling Ribonucleotide and Deoxyribonucleotide Pools Perturbed by Remdesivir in Human Bronchial Epithelial Cells - Li, Yan; Zhang, Hui-Xia; Luo, Wen-Di; Lam, Christopher Wai Kei; Wang, Cai-Yun; Bai, Li-Ping; Wong, Vincent Kam Wai; Zhang, Wei; Jiang, Zhi-Hong (Frontiers in Pharmacology, 2021)
Remdesivir (RDV) has generated much anticipation for its moderate effect in treating severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. However, the unsatisfactory survival rates of hospitalized patients limits its application to the treatment of coronavirus disease 2019 (COVID-19). Therefore, improvement of antiviral efficacy of RDV is urgently needed. As a typical nucleotide analog, the activation of RDV to bioactive triphosphate will affect the biosynthesis of endogenous ribonucleotides (RNs) and deoxyribonucleotides (dRNs), which are essential to RNA and DNA replication in host cells. The imbalance of RN pools will inhibit virus replication as well. In order to investigate the effects of RDV on cellular nucleotide pools and on RNA transcription and DNA replication, cellular RNs and dRNs concentrations were measured by liquid chromatography–mass spectrometry method, and the synthesis of RNA and DNA were monitored using click chemistry. Results showed that the IC50 values for BEAS-2B cells at exposure durations of 48 and 72 h were 25.3 ± 2.6 and 9.6 ± 0.7 μM, respectively. Ten (10) μM RDV caused BEAS-2B arrest at S phase and significant suppression of RNA and DNA synthesis after treatment for 24 h. In addition, a general increase in the abundance of nucleotides and a more than 2-fold increase of specific nucleotides were observed. However, the variation of pyrimidine ribonucleotides was relatively slight or even absent, resulting in an obvious imbalance between purine and pyrimidine ribonucleotides. Interestingly, the very marked disequilibrium between cytidine triphosphate (CTP) and cytidine monophosphate might result from the inhibition of CTP synthase. Due to nucleotides are also precursors for the synthesis of viral nucleic acids, the perturbation of nucleotide pools would block viral RNA replication. Considering the metabolic vulnerability of endogenous nucleotides, exacerbating the imbalance of nucleotide pools imparts great promise to enhance the efficacy of RDV, which possibly has special implications for treatment of COVID-19.